2017
DOI: 10.1111/ced.13213
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-17 in patients with erythema multiforme or Stevens-Johnson syndrome/toxic epidermal necrolysis drug reaction, and correlation with disease severity

Abstract: Serum IL-17 levels may have prognostic and diagnostic value in patients with EM or SJS/TEN reactions, and can provide a valuable approach in managment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
0
16
1
1
Order By: Relevance
“…Przepiorka‐Kosinska et al showed that serum IL‐17 levels positively correlated with psoriasis severity and Elghandour et al reported a significant decreased in serum IL‐17 levels in psoriasis patients after narrow band ultraviolet B and methotrexate therapies 35,36 . Serum IL‐17 concentrations also correlated with disease severity in patients with HS, vitiligo, SJS/TEN, and acne vulgaris 37,38,41,43 . Our result did not report any association between serum IL‐17 levels and disease features including rosacea subtype, disease severity, age of disease onset, disease duration, and presence of family history of rosacea.…”
Section: Discussioncontrasting
confidence: 63%
“…Przepiorka‐Kosinska et al showed that serum IL‐17 levels positively correlated with psoriasis severity and Elghandour et al reported a significant decreased in serum IL‐17 levels in psoriasis patients after narrow band ultraviolet B and methotrexate therapies 35,36 . Serum IL‐17 concentrations also correlated with disease severity in patients with HS, vitiligo, SJS/TEN, and acne vulgaris 37,38,41,43 . Our result did not report any association between serum IL‐17 levels and disease features including rosacea subtype, disease severity, age of disease onset, disease duration, and presence of family history of rosacea.…”
Section: Discussioncontrasting
confidence: 63%
“…16 In addition, some inflammatory cytokines, like TNFα, interleukin (IL)-15, and IL-17, were also related to it. 17,18 Genetic factors and offending medications can result in activation of an inflammatory cascade, leading to keratinocyte apoptosis, blistering, and systemic inflammation. 9 The traditional inflammatory parameters such as CRP and PCT have been used to evaluate systemic inflammatory status and prognosis in some hyper-inflammatory immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are favorable to the key role of granulysin, a product of CTLs and NK cells, in the pathogenesis of SJS/TEN. EM is a cutaneous reaction characterized by typical or atypical target lesions that mimic cutaneous manifestations of SJS/TEN in the early phase [2], [22], [23]. The causes of EM may be a viral infection or drug reaction [22], [23], [32].…”
Section: Discussionmentioning
confidence: 99%
“…EM is a cutaneous reaction characterized by typical or atypical target lesions that mimic cutaneous manifestations of SJS/TEN in the early phase [2], [22], [23]. The causes of EM may be a viral infection or drug reaction [22], [23], [32]. Serum granulysin can be also elevated in viral infected conditions [33] such as virus-associated EM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation